Enriched rehabilitation on brain functional connectivity in patients with post-stroke cognitive impairment - Yaping Huai; Weiwei Yang; Yichen Lv; Kui Wang; Hongyu Zhou; Yiqing Lu; Xiaoyun Zhang; Yaze Wang; Jibing Wang; Xin Wang (Frontiers in Neurology)
ObjectiveThis study aims to observe the effect of enrichment rehabilitation (ER) on cognitive function in post-stroke patients and to clarify its underlying mechanism.MethodsForty patients with post-stroke cognitive impairment (PSCI) meeting the inclusion criteria were randomly assigned to two groups: conventional medical rehabilitation (CM group) and ER intervention (ER group). All patients underwent assessments of overall cognitive function, attention function, and executive function within 24 h before the start of training and within 24 h after the 8 weeks of training. We investigated the altered resting-state functional connectivity (RSFC) with the right dorsolateral prefrontal cortex (DLPFC) in patients with PSCI following ER training through functional magnetic resonance imaging (fMRI). Additionally, twenty people undergoing routine physical examinations in the outpatient department of our hospital were selected as the healthy control (HC) group.ResultsBefore training, both groups of PSCI patients exhibited significant impairment in overall cognitive function, attention function, and executive function compared to the HC group. However, there was no significant difference between the two PSCI patient groups. Following 8 weeks of treatment, both PSCI patient groups demonstrated substantial improvement in overall cognitive function, attention function, and executive function. Moreover, the ER group exhibited greater improvement after training compared to the CM group. Despite the improvements, the cognitive behavioral performance assessment scores of both PSCI patient groups remained lower than those of the HC group. RSFC analysis in the ER group revealed strengthened positive functional connectivity between the right DLPFC and the left superior frontal gyrus (SFG) and left anterior cingulate gyrus (ACG), along with decreased functional connectivity between the right DLPFC and the right superior temporal gyrus (STG) and right precentral gyrus post-ER intervention.ConclusionER intervention is more effective than conventional medical rehabilitation in improving the cognitive function of PSCI patients, potentially by augmenting the FC between the right DLPFC and dominant cognitive brain regions, such as the left SFG and left ACG while attenuating the FC between the right DLPFC and non-dominant hemisphere areas including the STG and precentral gyrus within the right hemisphere.